Effects of Lactobacillus plantarum P9 Probiotics on Defecation and Quality of Life of Individuals with Chronic Constipation: Protocol for a Randomized, Double-Blind, Placebo-Controlled Clinical Trial. (13th June 2022) - Liu, Wenjun; Lu, Nong-Hua; Zhou, Xu; Li, Yingmeng; Xie, Yong; Zheng, Longjin; Zhu, Weifeng; Xiao, Qiuping; Yang, Ni; Zuo, Kexuan; Wu, Qingni; Xu, Tielong; et al.
Abstract : Background . Although probiotics have been shown to improve constipation-related symptoms, a clear consensus on the use of probiotics as a constipation-relieving agent has not been reached, which is attributed to the limited available evidence and inconsistent protocols used in existing studies. Method . A randomized, double-blind, placebo-controlled clinical trial is designed to study the efficiency and possible mechanism of action of probiotics for chronic constipation, in which 200 eligible volunteers with chronic constipation will be randomly assigned to a probiotic group (oral Lactobacillus plantarum P9 probiotic powder, 100 billion colony-forming units (CFUs)/day) or a placebo group. Volunteers, treatment distributors, data collectors, and data analysts will be blinded. The primary outcome is the weekly mean frequency of complete spontaneous bowel movements (CSBMs), and secondary outcomes include weekly mean frequency of CSBMs ≥3, weekly mean frequency of spontaneous bowel movements (SBMs), weekly mean stool appearance score, weekly mean difficulty of passing stool score, weekly percentage of volunteers who use auxiliary measures to assist with defecation (WPUAMA), quality-of-life (QOL) score, emotional status score, gut microbiome, and faecal metabolome. Each outcome measure will be assessed at the time points of preadministration (day 0), administration (day 14 and/or 28), and postadministration (day 42) to identify inter- and intragroup differences. Adverse events will be recorded to evaluate the safety of L. plantarum P9. Discussion . The protocol will provide methodological guidance for other similar studies, avoiding methodological bias and ultimately facilitating the formulation of consensus on the use of probiotics as a constipation-relieving agent. In addition, the results are more comprehensive than those of existing studies and may objectively and scientifically reflect the effectiveness of L. plantarum P9 on constipation. If the expected study findings are obtained, L. plantarum P9, taken as a probiotic, may become a complementary choice for chronically constipated patients. This trial is registered with Chinese Clinical Trial Registry (ChiCTR) (no. ChiCTR2000038396 ) registered on November 22, 2020, https://www.chictr.org.cn/showproj.aspx?proj=54024 .